«WUTHERING HEIGHTS» ON THE SCREEN: EXPLORING THE RELATIONS BETWEEN FILM ADAPTATION AND SUBTITLING - Almeida, Paula Ramalho; Pascoal, Sara Cerqueira; Cunha, Suzana Noronha (POLISSEMA – Revista de Letras do ISCAP, 2019)
This essay aims to confront the literary text Wuthering Heights by Emily Brontë with five of its screen adaptations and Portuguese subtitles. Owing to the scope of the study, it will necessarily afford merely a bird’s eye view of the issues and serve as a starting point for further research. Accordingly, the following questions are used as guidelines: What transformations occur in the process of adapting the original text to the screen? Do subtitles update the film dialogues to the target audience’s cultural and linguistic context? Are subtitles influenced more by oral speech than by written literary discourse? Shouldn’t subtitles in fact reflect the poetic function prevalent in screen adaptations of literary texts? Rather than attempt to answer these questions, we focus on the objects as phenomena. Our interdisciplinary undertaking clearly involves a semio-pragmatic stance, at this stage trying to avoid theoretical backdrops that may affect our apprehension of the objects as to their qualities, singularities, and conventional traits, based on Lucia Santaella’s interpretation of Charles S. Peirce’s phaneroscopy. From an empirical standpoint, we gather features and describe peculiarities, under the presumption that there are substrata in subtitling that point or should point to the literary source text, albeit through the mediation of a film script and a particular cinematic style. Therefore, we consider how the subtitling process may be influenced by the literary intertext, the idiosyncrasies of a particular film adaptation, as well as the socio-cultural context of the subtitler and target audience. First, we isolate one of the novel’s most poignant scenes – ‘I am Heathcliff’ – taking into account its symbolic play and significance in relation to character and plot construction. Secondly, we study American, English, French, and Mexican adaptations of the excerpt into film in terms of intersemiotic transformations. Then we analyze differences between the film dialogues and their Portuguese subtitles.